Meaning of caregiving in relationships of people living with HIV/AIDS - Ventura-Elías, Celina Dolores; González-Ortega, Yariela; Chaparro-Diaz, Lorena (Universidad y Salud, 2021)
Introducción: Human immunodeficiency virus (HIV) unexpectedly affects the daily lives of people and has an impact on their personal and family dimensions. Relationships become crucial in the caregiving experience and it is not yet known how they exist. Objective: To construct the theoretical approach that describes and explains the processes of person-to-person relationships in people with HIV/AIDS. Materials and methods: A quantitative study that applies grounded theory was carried out with 25 HIV patients from the Republic of El Salvador. Results: The basic social process has four variables: (i) recognizing shared risks and return to the family; (ii) knowing and sharing with others; (iii) moving between suffering and change; and (iv) harmonizing life and relationships. Conclusions: The experience of having HIV/AIDS demonstrates the capacity of human beings to make use of their freedom and make decisions in the midst of the alternating rhythms of suffering, which allows them to begin to find the meaning of life in an indeterminate period of time.